Isolation and characterisation of plant growth-promoting bacterial and fungal endophytes from Himalayan Yew (Taxus wallichiana) - an economically imperative pant of Himalayas - Sharief Khan, Sofia; Verma, Vijeshwar; Rasool, Shafaq (Penerbit Universiti Kebangsaan Malaysia, 2022)
It is a known fact that the bacterial and fungal endophytes inhabit the plant tissues besides aiding in the better growth and health of the plants. The bark and leaves of Taxus wallichiana have drawn a lot of interest in recent years since they are the richest source of taxol, an anticancer drug. As it is a slow-growing tree that can only be regenerated via vegetative propagation, it has been classified as a critical rare species due to its extensive collection for medicinal and other purposes. Nonetheless, the use of endophytes as plant growth promoters is gaining much importance among environmentalists and agronomists because of their imperative role in crop production. Even then, there is hardly any information available regarding the growth-promoting endophytes isolated from bark and leaves associated with T. wallichiana commonly known as Himalayan Yew. Therefore, the present study was undertaken to isolate fungal and bacterial endophytes from T. wallichiana and to classify the growth-promoting properties of these endophytes. In total, seven fungal and ten bacterial endophytes were obtained from different parts of T. wallichiana. All of the isolated fungal and bacterial endophytes produced indole acetic acid while most of them also produced ammonia. Besides, the fungal and bacterial endophytes were also screened for antimicrobial and various enzymatic activities. Based on the above results, the two fungal endophytes were selected for their possible ability to promote seed growth. The results showed that the fungal endophytes isolated from T. wallichiana played an active role in increasing growth in other plant species and therefore, can be used as potential plant growth promoters.